Feasibility and acceptability of injectable artesunate for the treatment of severe malaria in the Democratic Republic of Congo. (December 2016) - Ntuku, Henry; Ferrari, Gianfrancesco; Burri, Christian; Tshefu, Antoinette; Kalemwa, Didier; Lengeler, Christian
Abstract Background The Democratic Republic of the Congo (DRC) changed its national policy for the treatment of severe malaria in both children and adults in 2012 from intravenous quinine to injectable artesunate. The country is now planning to deploy nationwide injectable artesunate as the preferred treatment for the management of severe malaria. To support this process, the feasibility and acceptability of the use of injectable artesunate in the context of the DRC was assessed, from the perspective of both health care providers and patients/caretakers. Methods Questionnaires and observations were used to collect information from health care providers and patients/caretakers in eight health facilities in the Province of Kinshasa and in the Province of Bas-Congo. Results A total of 31 health care providers and 134 patients/care takers were interviewed. Seventy five percent (75 %) of health care providers found it less difficult to prepare injectable artesunate compared to quinine. None of them encountered problems during preparation and administration of injectable artesunate. The large majority of care providers (93 %) and patients/caretakers (93 %) answered that injectable artesunate took less time than quinine to cure the symptoms of the patients. 26 (84 %) health care providers reported that the personnel workload had diminished with the use of injectable artesunate. 7 (22.6 %) health workers reported adverse drug reactions, of which a decrease in the haemoglobin rate was the most common (71.4 %). All care providers and the vast majority of patients/caretakers (96 %, N = 128) were either satisfied or very satisfied with injectable artesunate. Conclusions These findings show that the use of injectable artesunate for the treatment of severe malaria is feasible and acceptable in the context of DRC, with appropriate training of care providers. Both care providers and patients/caretakers perceived injectable artesunate to be effective and safe, thus promoting acceptability.